Analysis of a biathlon sprint competition and associated laboratory determinants of performance - Talsnes, R.; Luchsinger, H.; Kocbach, J.; Sandbakk, O. (NVC Conference 2017, 5.-6. October 2017, Are, Sweden, 2017)
Biathlon is a winter-sport combining rifle shooting with crosscountry (XC) skiing using the skating technique. In the present study, we aimed to investigate the contribution of shooting and XC skiing performance to the overall biathlon sprint performance, as well as their relationships to laboratory-measured capacities obtained during treadmill roller skiing.